2017
DOI: 10.3892/mmr.2017.6312
|View full text |Cite
|
Sign up to set email alerts
|

Icariin inhibits MMP-1, MMP-3 and MMP-13 expression through MAPK pathways in IL-1β-stimulated SW1353 chondrosarcoma cells

Abstract: Osteoarthritis (OA) is the most common type of arthritis and is a leading cause of disability worldwide, resulting in pain, reduced quality of life and socioeconomic burden. Current therapies for OA focus on mitigating the symptoms of advanced disease, but novel therapeutic agents are needed to inhibit the processes leading to OA. The present study aimed to investigate the effects of Icariin on matrix metalloproteinase (MMP)‑1, MMP‑3 and MMP‑13 expression in interleukin (IL)‑1β‑stimulated human SW1353 chondros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…It has been reported that the IL-1β-induced increase in MMP-13 expression requires p38 activity, JNK activity, and NF-κB translocation but does not involve MEK, whereas the increase in MMP-1 expression requires p38 and MEK activity but does not involve JNK and NF-κB [79]. MMP-1 and MMP-3 expression in IL-1β-stimulated chondrosarcoma cells was suppressed by p38 and ERK inhibitors but not by JNK inhibitor, and MMP-13 expression was suppressed by p38 and JNK inhibitors but not ERK inhibitor [80]. These findings indicate that the signaling pathway for IL-1β-mediated regulation of MMP-13 is different from that for IL-1β-mediated regulation of MMP-1 and MMP-3 and may not involve MEK/ERK activities.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that the IL-1β-induced increase in MMP-13 expression requires p38 activity, JNK activity, and NF-κB translocation but does not involve MEK, whereas the increase in MMP-1 expression requires p38 and MEK activity but does not involve JNK and NF-κB [79]. MMP-1 and MMP-3 expression in IL-1β-stimulated chondrosarcoma cells was suppressed by p38 and ERK inhibitors but not by JNK inhibitor, and MMP-13 expression was suppressed by p38 and JNK inhibitors but not ERK inhibitor [80]. These findings indicate that the signaling pathway for IL-1β-mediated regulation of MMP-13 is different from that for IL-1β-mediated regulation of MMP-1 and MMP-3 and may not involve MEK/ERK activities.…”
Section: Discussionmentioning
confidence: 90%
“…ICA, the extract of Epimedium, is known to have anti-oxidative, anti-neuroinflammatory, and anti-apoptotic effects and considered to be effective for a range of disorders, such as neoplasm, Alzheimer's disease, cerebral ischemia, depression, diabetes, and Parkinson's disease (PD) [22][23][24][25]. For OA, ICA was identified as an anti-osteoporotic and anti-inflammatory compound through multi-target mechanisms, including the suppression of NF-κB signaling and inhibition of MMP1, MMP3, and MMP13 expression or OPG-RANKL-RANK system via MAPK pathways [13][14][15]. The present study demonstrated that ICA inhibited LPS-mediated chondrocytes injury and pyroptosis and alleviated rat osteoarthritis by inhibiting NLRP3 and caspase-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that ICA prevented OA inflammation and chondrocytes apoptosis though activation of autophagy via inhibiting NF-κB signaling pathway [13]. Furthermore, ICA exerted a chondroprotective effect through the inhibition of MMP-1, MMP-3, and MMP-13 or the suppression of osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL), and receptor activator of nuclear factor kappa-B (RANK) system via MAPK pathway in IL-1β-stimulated chondrosarcoma cells [14,15]. However, the molecular mechanisms of ICA alleviating OA and its relationship with NLRP3 inflammasome are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the MAPK signaling pathway may lead to the secretion of several matrix-degrading proteinases, including the MMPs and the aggrecanases, leading to articular cartilage breakdown. IL-1β, the major proinflammatory cytokine involved the progression of OA, can easily activated the MAPK pathways ( 27 , 28 ). Thus, in our study, we investigated whether the anti-inflammatory effects of Kaempferol were through the attenuation of MAPK.…”
Section: Discussionmentioning
confidence: 99%